Killing of the Women for Honor Reason in Kurdish Society: Descriptive Study (Raparin Journal of Humanities (RJH), 2025)
The killing of women in Kurdish society because of the issue of honor is a complex social phenomenon that depends on historical social traditions and values. The concept of honor is defined, in this context, as being linked to women’s behavior and sexual behavior, and it requires women to adhere to strict social laws related to chastity and traditions. Killing women because of honor is considered an embodiment of domestic violence and discrimination against women in Kurdish societies and other regions, and this phenomenon is not limited only to Kurdish society, but is also spreading in other regions around the world in different forms. This phenomenon has been linked to the content of culture and tradition, and honor is considered sacred and must be preserved at all costs. Therefore, if a woman’s behavior is considered to violate this honor, it can have serious consequences, including murder and sexual discrimination, and women are treated with discrimination, as They are prevented from obtaining education and working outside the home, making them more vulnerable to abuse and control, as well as honesty and transparency. In some cases, men are required to maintain the “family trust,” making them responsible for the behavior of their family members, and this can include monitoring and restricting women’s freedom. . The researcher concluded that this phenomenon may be due to the presence of weak laws in some places. The penalties for honor killings of women are minimal or ineffective, which enhances the continuation of this type of violence. The researcher recommended that, in order to combat this phenomenon, ideas and values must be changed. Social practices, promoting women’s rights, education and awareness of their rights, and calling for tougher penalties for crimes of violence against women in domestic and international laws.